Labor Exploitation in HR Management Wage Receipts U.D Karyati Jaya Tangerang - South - Suyanto, Agus; Irwansyah , Novi; Riyanto, Slamet; Setiawan, Aries; Kumar, Saurav (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The aim of this research is to determine the exploitation of workers in receiving wages from an Islamic economic perspective (case study at UD Karyati Jaya Tangerang - South). This type of research is descriptive qualitative. The data sources used by researchers are primary and secondary. Data collection methods use interviews, observation, documentation. The technique for guaranteeing data validity uses deductive thinking. Empirical qualitative research methods. field observation, studying, analyzing, interpreting, and drawing conclusions. The research results show that at UD Karyati Jaya Tangerang - South the work carried out by workers at UD. Karyati Jaya has been said to be good and in line with expectations, they have fulfilled their obligations as workers and are in accordance with the applicable theories regarding the obligations that workers should carry out, namely: (a) Doing the work themselves as stated in the agreement. (b) Work according to the agreed time. (c) Doing work diligently. However, the rights received by workers are not in accordance with applicable humanitarian theory and customs, they work well according to the regulations set, the applicable working hours are carried out in an orderly manner, but the wages they receive are not in accordance with the effort they put in.